2007
DOI: 10.1021/jp070212j
|View full text |Cite
|
Sign up to set email alerts
|

A Lumry−Eyring Nucleated Polymerization Model of Protein Aggregation Kinetics:  1. Aggregation with Pre-Equilibrated Unfolding

Abstract: A mathematical model is presented of the kinetics of non-native protein aggregation that combines Lumry-Eyring and nucleated polymerization (LENP) descriptions. The LENP model is solved for cases in which aggregation rates are slow compared to folding-unfolding equilibration and is shown to be a generalization of a number of previously proposed nucleation-and-growth models for non-native and native protein aggregation. The model solutions exhibit a number of qualitative kinetic regimes. Each regime has a chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
394
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(421 citation statements)
references
References 71 publications
20
394
0
1
Order By: Relevance
“…1) Lumry-Eyring model, according to which a native protein unfolds in a reversible way into an unfolded state which then aggregates irreversibly [6], [7] 2) Native polymerization models, in which nucleation and polymer growth are treated in detail, but conformational changes prior to or during assembly are not included [5], [8] 3) Extended Lumry-Eyring models, in which aggregation kinetics observed experimentally, are described as a combination of reversible conformational transitions and the intrinsic kinetics via non native states. However, in contrast to classical Lumry Eyring model, these models include a detailed description of the intrinsic aggregation kinetics [9] 4) Aggregate condensation and polymerization models, which specifically take care of the higher order assembly of aggregates that are formed during the initial steps of nucleation and polymerization [5], [10] The modified Lumry Eyring kinetic model has been successfully used by researchers to describe the monoclonal antibody aggregation process at low pH (3-4) [6].…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…1) Lumry-Eyring model, according to which a native protein unfolds in a reversible way into an unfolded state which then aggregates irreversibly [6], [7] 2) Native polymerization models, in which nucleation and polymer growth are treated in detail, but conformational changes prior to or during assembly are not included [5], [8] 3) Extended Lumry-Eyring models, in which aggregation kinetics observed experimentally, are described as a combination of reversible conformational transitions and the intrinsic kinetics via non native states. However, in contrast to classical Lumry Eyring model, these models include a detailed description of the intrinsic aggregation kinetics [9] 4) Aggregate condensation and polymerization models, which specifically take care of the higher order assembly of aggregates that are formed during the initial steps of nucleation and polymerization [5], [10] The modified Lumry Eyring kinetic model has been successfully used by researchers to describe the monoclonal antibody aggregation process at low pH (3-4) [6].…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, in contrast to classical Lumry Eyring model, these models include a detailed description of the intrinsic aggregation kinetics [9] 4) Aggregate condensation and polymerization models, which specifically take care of the higher order assembly of aggregates that are formed during the initial steps of nucleation and polymerization [5], [10] The modified Lumry Eyring kinetic model has been successfully used by researchers to describe the monoclonal antibody aggregation process at low pH (3-4) [6]. A mathematical model of non-native protein aggregation has also been presented which combines the Lumry Eyring and Nucleated Polymerization (LENP) descriptions that is useful under conditions where detailed kinetics of folding or unfolding can be neglected [5]. However, a detailed study of aggregation behavior of monoclonal antibodies at several different conditions of pH, temperature and salt molarity pertaining to different types of chromatography could not be found in the literature and this work is an attempt to address the same by analyzing the stability of monoclonal antibodies under the different experimental conditions employed for Protein A chromatography, Cation Exchange Chromatography and Anion Exchange Chromatography.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The long term loss of monomer is generally predicted through quantitative monitoring of aggregation under accelerated and stress conditions over weeks to months. Recent progress has been made in: (i) the development of detailed kinetic models [2,4,5,34,42,49,60,96]; (ii) correlating aggregation kinetics with protein structure and folding [11,15,16,32,35,52,53,54,67,88]; (iii) and with native-state protein-protein interaction measurements [36,46,57,74,75,79,82].…”
Section: Introductionmentioning
confidence: 99%
“…32,33 Equilibrium may also exist between smaller and larger aggregates on static storage of stressed samples. It has also been reported that visible and subvisible particles generated by shake stress could be reversible and may dissociate into smaller aggregates over time.…”
Section: Stability Of Submicron Particles and Repeatability Of Nta Anmentioning
confidence: 99%